Optical rectification in doped GaSe crystals - Lanskii, Grigory V.; Kokh, Konstantin A.; Svetlichnyi, Valerii A.; Andreev, Yury M. 1946- (Key engineering materials)
It was demonstrated that S- and Te-doped GaSe crystals are useful and prospective for mid-IR and THz generation by optical rectification as well as phase matched mixing of spectral components of the fs pulse (down conversion). Phase matching curves for down-conversion in the S-doped and Te-doped GaSe. The sample optimally doped with sulfur (2.5 mas. %) have shown better characteristics under high pump fluencies than ZnTe material used in commercial devices.